2008
DOI: 10.1029/2007jd009046
|View full text |Cite
|
Sign up to set email alerts
|

Parametric model to estimate clear‐sky longwave irradiance at the surface on the basis of vertical distribution of humidity and temperature

Abstract: [1] The surface downwelling longwave irradiance in clear-sky situations is an important component of the global radiation balance. It can be measured directly using ground-based pyrgeometers or computed using a radiative transfer code given precise information on atmospheric composition (water vapor, ozone, and aerosols) and temperature. Discrepancies between instantaneous observed and simulated values of the clear-sky longwave irradiance are typically at the 3-10 W m À2 level (root-mean-square error). The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
(88 reference statements)
2
25
0
Order By: Relevance
“…The effective emissivity depends on the vertical structure of the atmosphere and those formulae that only rely on surface information must be applied with caution. Several authors evidenced different behaviour of the empirical parameterisations when applied to day time or night time data (Paltridge, 1970;Arnfield, 1979;AladosArboledas and Jiménez, 1988;Tang et al, 2004;Dupont et al, 2008), with an overestimation effect during the day time. Alados-Arboledas (1993) showed that the use of a single expression based on screen level variables for the whole day requires the inclusion of a day-night correction term, taking into account the day-night differences in the vertical structure of the atmosphere and thus the effective emissivity regime.…”
Section: Parameterisations With Locally Fitted Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective emissivity depends on the vertical structure of the atmosphere and those formulae that only rely on surface information must be applied with caution. Several authors evidenced different behaviour of the empirical parameterisations when applied to day time or night time data (Paltridge, 1970;Arnfield, 1979;AladosArboledas and Jiménez, 1988;Tang et al, 2004;Dupont et al, 2008), with an overestimation effect during the day time. Alados-Arboledas (1993) showed that the use of a single expression based on screen level variables for the whole day requires the inclusion of a day-night correction term, taking into account the day-night differences in the vertical structure of the atmosphere and thus the effective emissivity regime.…”
Section: Parameterisations With Locally Fitted Coefficientsmentioning
confidence: 99%
“…Most of these parameterisations were derived for night-time data using local empirical coefficients (Brunt, 1932;Idso and Jackson, 1969;Brutsaert, 1975;Idso, 1981). Several authors (Paltridge, 1970;Berdahl and Fromberg, 1982;Alados-Arboledas and Jiménez, 1988;Alados-Arboledas, 1993;Dupont et al, 2008) pointed out the differences between the day and night effective emissivity regimes. Results of this type suggest that the evaluation of various LW parameterisations covering the complete daily cycle would provide useful information for a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the MODIS TOA brightness temperature errors are 0.25 K for channels 28, 33, 34 and 35, 0.05 K for channels 29, 31 and 32, and 0.35 K for channel 36, respectively, δ(L DSLR ) can be acquired with Equation (8). Here, we adopted an uncertainty of the WVC for MODIS product of 0.5 g/cm 2 [64], so the corresponding DSLR AOD errors for VZA = 0 • and z = 0 km are as follows.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…DSLR is the result of atmospheric scattering, absorption and emission in the entire vertical column, and it can be accurately calculated with complex radiative transfer models for which the concentrations of atmospheric constituents and the vertical distribution of temperature, water vapor, aerosol and clouds as the input parameters [4][5][6][7]. It is therefore necessary to evaluate accurately these parameters if one wants to reduce uncertainties in computing their radiative effects [8,9]. However, acquisition of these parameters is difficult and they are varying rapidly, at a daily or even hourly scale.…”
Section: Introductionmentioning
confidence: 99%
“…Ruckstuhl et al (2007) showed that the monthly mean LDR can be effectively modeled from specific humidity or water vapor obtaining differences < 5 %. Dupont et al (2008) presented a more sophisticated parameterization based on the vertical profiles of temperature and humidity obtaining uncertainties of ∼ 5 W m −2 for cloud-free conditions, for both daytime and night-time.…”
Section: R D García Et Al: Comparison Of Observed and Modeled Ldr mentioning
confidence: 99%